2006
DOI: 10.1211/jpp.58.1.0002
|View full text |Cite
|
Sign up to set email alerts
|

Statins and osteoporosis: new role for old drugs

Abstract: Osteoporosis is the most common bone disease, affecting millions of people worldwide and leading to significant morbidity and high expenditure. Most of the current therapies available for its treatment are limited to the prevention or slowing down of bone loss rather than enhancing bone formation. Recent discovery of statins (HMG-CoA reductase inhibitors) as bone anabolic agents has spurred a great deal of interest among both basic and clinical bone researchers. In-vitro and some animal studies suggest that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(105 citation statements)
references
References 121 publications
1
98
0
6
Order By: Relevance
“…Expression of this gene is also modulated by the peroxisome proliferator-activated receptor (PPAR)-g2 transcription factor that has been shown to interfere with age-related bone loss via the activation of adipogenic and suppression of osteogenic programs of mesenchymal stem cells (31). Our results strengthen the putative connection between bone and lipid metabolism (32)(33)(34); however, further studies are needed to clarify the role of FABP3 and its genetic variations in the pathomechanism of bone loss.…”
Section: Discussionsupporting
confidence: 60%
“…Expression of this gene is also modulated by the peroxisome proliferator-activated receptor (PPAR)-g2 transcription factor that has been shown to interfere with age-related bone loss via the activation of adipogenic and suppression of osteogenic programs of mesenchymal stem cells (31). Our results strengthen the putative connection between bone and lipid metabolism (32)(33)(34); however, further studies are needed to clarify the role of FABP3 and its genetic variations in the pathomechanism of bone loss.…”
Section: Discussionsupporting
confidence: 60%
“…Additional evidence that statins may have an antiresorptive effect has been shown by Woo et al (2000) using an in vitro assay for osteoclast formation (Takahashi et al 1988), suggesting that statins also exert inhibitory effects on the differentiation of osteoclasts by interfering with the fusion process by which osteoclast precursors develop into multinucleated osteoclast-like cells. Many clinical studies have suggested that statin use is associated with a reduced risk of bone fractures; however, only a modest increase in bone mass and inconsistent effects on bone turnover have been reported to date (Bauer 2003, Jadhav & Jain 2006. Given that !5% of an oral dose statin reaches the systemic circulation (Bellosta et al 2000), osteoblasts and osteoclasts are exposed to very low concentrations of statin with usual oral regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that simvastatin also has an effect on bone metabolism. Simvastatin has been found to increase bone formation (Mundy et al, 1999;Staal et al, 2003;Jadhav and Jain, 2006) by promoting osteoblast differentiation and mineralization (Maeda et al, 2001). Simvastatin may also inhibit the RANKL-induced NF-κB activation pathway that leads to suppression of osteoclastogenesis (Ahn et al, 2008) and inhibits induction of matrix metalloproteinase-9 which is related to bone resorption (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%